2001
DOI: 10.18388/abp.2001_5108
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of cysteine proteases and their inhibitors.

Abstract: Cysteine proteases (CPs) are responsible for many biochemical processes occurring in living organisms and they have been implicated in the development and progression of several diseases that involve abnormal protein turnover. The activity of CPs is regulated among others by their specific inhibitors: cystatins. The main aim of this review is to discuss the structure-activity relationships of cysteine proteases and cystatins, as well as of some synthetic inhibitors of cysteine proteases structurally based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
2
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 95 publications
(87 reference statements)
3
84
2
7
Order By: Relevance
“…The best characterized family of cysteine proteases is the 'papain' that includes mammalian lysosomal cathepsin where the 'papain-fold' catalytic dyad (Cys25-His159) is evolutionarily preserved in all known eukaryotic papain-like cysteine protaseses (Grzonka et al, 2001). In HCoV-229E PL1pro, the conserved catalytic 'Cys1054-His1205' dyad was found to be indispensable for its proteolytic activity (Herold et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best characterized family of cysteine proteases is the 'papain' that includes mammalian lysosomal cathepsin where the 'papain-fold' catalytic dyad (Cys25-His159) is evolutionarily preserved in all known eukaryotic papain-like cysteine protaseses (Grzonka et al, 2001). In HCoV-229E PL1pro, the conserved catalytic 'Cys1054-His1205' dyad was found to be indispensable for its proteolytic activity (Herold et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Proteases are classified according to their catalytic site into four major classes: cysteine (thiol) proteases, serine proteases, aspartyl (acid) proteases, and metalloproteases. Of the 21 families of cysteine proteses discovered so far, almost half of them are coded by viruses (Grzonka et al, 2001). The best characterized family of cysteine proteases is the 'papain' family characterized by a two-domain structure that contains an active site (catalytic pocket) for substrate binding.…”
Section: Introductionmentioning
confidence: 99%
“…Cystatin C is the inhibitor of cysteine proteases [27]. It could be regulated by ubiquitin through IRF8 in the networks.…”
Section: D-dige and Uplc-q/tof Ms Showed Decrease In The Ms Groupmentioning
confidence: 99%
“…8 In addition, this conserved cysteine was of interest given that it was not observed in a conserved motif commonly associated with either formation of disulfide bonds used in structure stabilization, 9 iron-sulfur clusters, 10 redox control, 11 or nucleophilic activity, such as in cysteine proteases. 12 Taken together, this information indicated that the conserved cysteine found at position 127 (M. jannaschii numbering) may have an important role in either the enzymatic activity or structure of Ade's and thus the role of this cysteine was investigated. A combination of experimental and computational approaches was used to provide insight into the potential role of the conserved cysteine at position 127 in M. jannaschii.…”
Section: Introductionmentioning
confidence: 97%